PENGELOLAAN RETRIBUSI PASAR KOTA TERNATE TAHUN 2006-2010 - , Bianci Rais ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research was conducted in Ternate city, the objectives to be achieved in this study were to unveil the contribution of market levy towards local levies and Locally Derived Revenue (PAD), the target growth and the realization of market levy, the target growth and the realization of local levies, the effectiveness and efficiency in the collection of market levy, also to indentify the weak factor, the strength factor, the opportunity and threat factor in the market levy management. This research used the contribution formulation, the growth, the effectiveness and efficiency, and the SWOT analysis. The results of this research showed that the contribution of market levy to the local levies in 2006 till 2010 was average at 30.24 percent, while the contribution of market levy to the Locally Derived Revenue (PAD) was average at 11,35 percent. The target change of market levy was average at 22,29 percent and the target change of local levies was average at 19,46 percent, whereas the change of market levy realization was average at 22,19 percent and the change of local levies realization was average at 17,23 percent. The effectiveness during the study period was average at 98,97 percent, while the average efficiency was average at 21,29 percent. The SWOT analysis result on the market levy management of Ternate city located in the fourth quadrant, that was the strategic diversification, i.e in the quadrant that Municipal Government of Ternate should create some strategies which uses its power to address the existing threats.